Asas Kontradiktur Delimitasi dalam Penandatanganan Batas Bidang Tanah pada Pendaftaran Tanah - Khairatunnisa; Djoni Sumardi Gozali (Lembaga Yasin AlSys, 2026)
Although the contradictory delimitation principle has received attention in various studies on land registration, research specifically addressing the timing of the signing of land parcel boundaries and its legal consequences remains limited. This study aims to analyze the regulation of the timing of the signing of land parcel boundaries in the land registration process based on the contradictory delimitation principle and to examine the legal consequences arising when this principle is not implemented. This study employed a normative legal research method using statutory and conceptual approaches. The legal materials consisted of primary, secondary, and tertiary legal materials, which were analyzed qualitatively using a prescriptive method. The findings indicate that Government Regulation Number 24 of 1997 stipulates that boundary approval and signing are conducted during field measurements with the direct involvement of adjoining landowners. Meanwhile, Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 16 of 2021 shifts the signing of boundaries to the pre-application stage through the Statement Letter on the Installation of Boundary Markers and Approval of Adjoining Landowners as an administrative requirement. Although implemented at different stages, both regulations share the same objective, namely to ensure legal certainty and prevent disputes over land parcel boundaries. Failure to implement the contradictory delimitation principle may create legal uncertainty regarding land parcel boundaries, increase the potential for land disputes, reduce legal protection for the parties, and result in administrative defects that render certificates vulnerable to annulment. This study contributes to the development of agrarian law scholarship and provides practical recommendations for strengthening land administration procedures to ensure legal certainty and prevent disputes over land parcel boundaries.